The High-speed Fabric Defect Detection Algorithm Based on the Image Layered Model (Journal of Fiber Bioengineering and Informatics, 2013)
The high-speed fabric defect detection algorithm based on fabric image layered model is proposed toachieve the goal of accurate defect detection in the fabric production process. The image layered modelassumes that fabric image is a superposition of the periodic texture background image, noise image,and defect image. Thus fabrics can be divided and conquered. Firstly, image preprocessing and meansampling algorithms were used to suppress the background texture and interference image layer, andvariances sampling was used for enhancing defect image layer. Secondly, the Otsu method was appliedfor determining the segmentation threshold to segment the defect image automatically, then clear andaccurate defect image was obtained via image post-treatment algorithm. Finally, defect positions weremarked by a labeling algorithm to prepare for subsequent offine processing. Experiments on commondefect images from a standard defect library were described, and experimental results show that theproposed algorithm based on image layered model is reliable, accurate, real-time and well used in theindustrial field.